The Explicit Animal - Tallis, R. author. aut Link
XVI, 313 p.
Keywords: Criticizes attempts to "biologize" consciousness by explaining its origin in evolutionary terms and identifying mental phenomena with brain processes, to "computerize" it by identifying mind with the supposed computational activity of the brain, and to eliminate it by denying the reality of qualia.